USER RESPONSES ABOUT AUTOMATED SYSTEM FOR CIRCULATION SERVICES AT UTHMAN BIN AFFAN LIBRARY, MUSLIM UNIVERSITY OF INDONESIA - Syakhrul Ikhsan; La Ode Ismail Ahmad; Nur Arifin (Pascasarjana UIN Alauddin Makassar, 2022)
The purpose of this study is to describe how the response of users about automation in the Uthman bin Affan library at the Indonesian Muslim University. This type of research is using qualitative research or field research. The research location is in the Uthman bin Affan library at the Indonesian Muslim University. There are two sources of data in this study, namely secondary data sources and primary data sources. The methods in collecting research data are Observation, Interview and Documentation using Data Processing and Analysis Techniques Data Reduction, Data Presentation and Conclusion Drawing. The results of this study are the responses of the users about the automation system in the Uthman Bin Affan Library, Muslim University of Indonesia are: a. the ease of finding library materials in the circulation service at the Uthman Bin Affan Library of the Muslim University of Indonesia is very easy and fast. b. The process of borrowing library materials, returning library materials, making membership cards, paying fines and visitor statistics is very easy and satisfying, but the automation system implemented at the Uthman Bin Affan library at the Muslim University of Indonesia has not been able to extend the borrowing of library materials or collections online. and the infrastructure is still lacking such as a computer or laptop. c. transactions for borrowing library materials do not use self-service machines. d. there are still many users who have not mastered the OPAC search service (online public access catalog) this is due to the lack of socialization to users, especially new users. The implications of the research are expected for librarians at the Uthman Bin Affan Library, Muslim University of Indonesia to maintain their services by using the slims automation system, the excellent service carried out by librarians in the circulation section has a positive impact on users, including the process of returning library materials, borrowing library materials, making membership cards library, fines, visitor statistics, friendliness of librarians, greeting librarians in providing information, speed in serving users, and the neat arrangement of library materials on the collection shelf are very satisfying in the hearts of users. towards officers in circulation services in order to improve the quality of their services and the Uthman Bin Affan Library of the Muslim University of Indonesia should recruit members for additional librarian officers in circulation services so that the service process in the circulation section is further improved.